Comparative transcriptome analysis reveals a serotype-specific immune response in Nile tilapia (Oreochromis niloticus) infected with Streptococcus agalactiae - Appel, Renan José Casarotto; Siqueira, Karine Nicole; Konstantinidis, Ioannis; Martins, Maria Isabel Mello; Joshi, Rajesh; Pretto-Giordano, Lucienne Garcia; Vilas-Boas, Laurival Antônio; Fernandes, Jorge Manuel de Oliveira (Frontiers in Immunology, 2025)
Streptococcus agalactiae is a major causative agent of streptococcosis in Nile tilapia (Oreochromis niloticus) and understanding its etiology is important to ensure the sustainable development of global tilapia farming. Our research group recently observed contrasting disease patterns in animals infected with two different S. agalactiae serotypes (Ib and III). To better understand the basis for these divergent responses, we analyzed the brain transcriptome of Nile tilapia following bacterial exposure. Our findings revealed significant variation in the expression of genes involved in immune (e.g., CD209 antigen, granulin, C-X-C motif chemokine 10, prostacyclin synthase, and interleukins) and neuroendocrine (e.g., mmp13a, mmp9, brain aromatase, and pmch) pathways. The serotype Ib strain seems promptly recognized by the host, triggering a potent inflammatory response, whereas the serotype III strain elicited a less immediate response, resulting in more pronounced central nervous system (CNS) symptoms and behavioral effects. To the best of our knowledge, this is the first study to show serotype-specific immune responses to S. agalactiae in Nile tilapia. These findings are important for advancing disease management and control strategies in aquaculture. Identifying different immune reactions triggered by serotypes Ib and III may assist the development of more specific approaches for preventive measures, early detection, and effective treatment against streptococcosis.